Rearrangement of a Transient Gold Vinylidene into Gold Carbenes. Issue 18 (13th March 2017) - Debrouwer, Wouter; Fürstner, Alois
Abstract: The gold acetylide complex20 endowed with a biaryl backbone provides opportunities for a study on the formation and fate of gold vinylidenes. Although the formyl group in20 is not sufficiently electrophilic to get attacked by the acetylide in proximity, its activation with TBSOTf (TBSOTf= tert ‐butyldimethylsilyl trifluoromethanesulfonate) at low temperature triggered instantaneous formation of a gold vinylidene (21 ). This metastable species evolved into the cationic gold carbene complex22 bearing a phenanthrene unit and a hydroxyl group at the aurated center; the recorded data suggest that this product might be better viewed as an acylgold species protonated by triflic acid. The use of [Me3 O⋅BF4 ] as the activating agent led to formation of the analogous Fischer‐type carbene24, whereas replacement of gold by the [CpRu(PPh3 )2 ] + fragment allowed the ruthenium vinylidene27 to be isolated, which closely resembles the proposed gold intermediate21 . The starting gold complex20, the derived products22 and24, as well as vinylidene27 were characterized by X‐ray diffraction. Abstract : Metamorphosis : An aldehyde is not electrophilic enough per se to be attacked by a gold acetylide, but activation with a Lewis acid triggers spontaneous formation of a gold vinylidene, which evolves into a Fischer gold carbene; the recorded data suggest that this product might actually be better viewed as an acylgold complex protonated by triflic acid.